2019
DOI: 10.1038/s41427-019-0129-7
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of 3D multifunctional microelectronic devices: challenges and opportunities

Abstract: Sophisticated three-dimensional (3D) forms are expected to be one of the significant development trends in nextgeneration microelectronics because of their capabilities of rendering substantially enhanced performances, a high degree of integration, and novel functionalities. To date, a diversity of manufacturing methods has been developed for 3D microelectronic devices with different structural and functional features. Most of these methods fall into two categories, i.e., micromanufacturing technologies and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…The buffer layer strategy can also be extended to the islandbridge systems consisting of 3D helical interconnects formed by the mechanically guided assembly techniques (see Figure 6a), as reported in recent years. [69][70][71][72][73][74][75][76][77][78][79][80][81] 3D helical interconnects have shown superior performances in compliance as well as stretchability. [18,61,82] However, in some application scenarios such as when brittle functional materials (e.g., highly doped silicon for thermoelectric coils [26,27] ) with ultra-low fracture strain apply, the compliance of the helical interconnect is severely restricted and therefore needs to be optimized.…”
Section: D Helical Interconnectsmentioning
confidence: 99%
“…The buffer layer strategy can also be extended to the islandbridge systems consisting of 3D helical interconnects formed by the mechanically guided assembly techniques (see Figure 6a), as reported in recent years. [69][70][71][72][73][74][75][76][77][78][79][80][81] 3D helical interconnects have shown superior performances in compliance as well as stretchability. [18,61,82] However, in some application scenarios such as when brittle functional materials (e.g., highly doped silicon for thermoelectric coils [26,27] ) with ultra-low fracture strain apply, the compliance of the helical interconnect is severely restricted and therefore needs to be optimized.…”
Section: D Helical Interconnectsmentioning
confidence: 99%
“…[ 6 ] Despite the central role played by silicon‐based devices in computing history, [ 7 ] it is nowadays accepted that bottom‐up technology may contribute to the development of new materials at the molecular scale exploiting atoms and molecules as computing building blocks. [ 8,9 ] Besides the obvious gain in integration, the route toward molecular computing can be environmentally friendly with reduced production costs, compared to the current silicon technology. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…[6] Despite the central role played by silicon-based devices in computing history, [7] it is nowadays accepted that bottom-up technology may contribute to the development of new materials at the molecular scale exploiting atoms and molecules as computing building blocks. [8,9] Besides the obvious gain in integration, the route toward molecular computing can be environmentally friendly with reduced production costs, compared to the current silicon technology. [10] The concept of atom-by-atom assembling to create molecules resembling traditional electronic components is not new [11] and has gained relevance since 1974 with the seminal paper of Ratner et al on a molecular rectifier using a single organic molecule.…”
mentioning
confidence: 99%
“…In microelectronics, insulating materials that can be used to generate high-density and high-speed integrated circuits for enhancing performance, are typically required to separate the conducting parts from each other and sustain the mechanical structures of chips. [1][2][3][4][5][6] Various types of porous materials including silica and zeolite type frameworks, [7,8] fluorinated carbons, [9][10][11] organic polymers, [12,13] etc., currently dominate the field of interlayer dielectrics in microelectronic chip devices; however, their relatively low dielectric constant, brittleness, thermal stability and large static power dissipation limit their practical applications. [7][8][9][10][11][12][13] The International Technology Roadmap for Semiconductors (ITRS) has suggested that desirable materials for promoting novel low k-dielectrics should have the capability of forming a crystalline structure, have a high elastic modulus (> 3 GPa), reduced pore size (< 5 nm), hydrophobicity and a high chemical and thermal stability.…”
Section: Introductionmentioning
confidence: 99%